ANALISIS PENGARUH HARGA, KUALITAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS KONSUMEN LAPIS TUGU MALANG ) - M. Bahrul Ulum; N. Rachma; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine the effect of price, product quality and location on purchasing decisions of Lapis Tugu Malang. The sample and population in this study were 80 respondents who were consumers who had bought Lapis Tugu Malang.The method used is descriptive data analysis, namely by using the tests of validity, reliability, normality, multicollinearity test, heterocedasticity test and hypothesis test t. The results of this study indicate that the variable price, product quality and location have a significant effect on purchasing decisions.Keywords: Price, Product Quality, Location and Purchasing Decision